You've found Oliver - Thao, Dustin (Dutton Books, 2025)
Fall in love all over again with Oliver's story in the hotly-anticipated companion to bestselling sensation You've Reached Sam. It's been a year since his best friend, Sam, died. Even though Oliver knows he won't get a response, he can't stop texting Sam's number, especially as the anniversary of his death approaches. Then one day he accidentally hits the call button, and someone picks up. The voice on the other end isn't Sam. Sam's number was reassigned and a stranger has been receiving Oliver's private and vulnerable messages for months. But Ben, a college student in Seattle, won't remain a stranger for long. When they finally meet in person, their spark is undeniable. Everything seems perfect until Oliver discovers something strange might be keeping them apart. Dustin Thao's star-crossed return to Ellensburg, WA is a sliding-doors romance sure to break your heart wide open.